Strategic integration of technology to foster students’ learning outcomes and motivation in legal English lessons - La Nguyen Binh Minh (Studies in English Language and Education)
This research aims to examine the correlation between the strategic utilization of technology in teaching legal English, a type of English for Specific Purposes (ESP), and students’ motivation. To achieve this aim, experimental research was designed and carried out over a semester (15 weeks) with the participation of 52 first-year students majoring in International Business and Trade Law. They were randomly and evenly divided into the Treatment group and the Control group which received teaching methods using technology and traditional teaching methods respectively. The data were obtained using pre- and post-achievement tests and a motivation questionnaire and then analyzed by using IBM SPSS software v26.0. The findings reveal that the use of technology in legal English lessons has significantly enhanced students’ academic performance. With reference to motivation, such methods resulted in an overall increase in students’ motivation from a pre-treatment moderate level to a post-treatment high level. Remarkably, the motivational factors positively affected by instructional technologies are intrinsic motivation, personal relevance, self-efficacy, assessment anxiety, and self-determination. However, there was no statistically significant change in students’ extrinsic motivation before and after the intervention, which was found to be high in the pre- and post-survey. Based on the results, this study advocates for the well-planned, systematic use of technology to teach legal English in particular and ESP in general.